2015
DOI: 10.5210/fm.v20i6.5505
|View full text |Cite
|
Sign up to set email alerts
|

The social significance of the Facebook Like button

Abstract: In this paper we study social aspects of using the Like button for purposes of impression management, identity construction, and maintenance of social ties online. On the theoretical level our investigation combines Goffman’s notion of face-work with concepts of social network analysis, shedding light on what we dub ‘nano-level’ interaction and sociality on social networking sites. Our data come from a 2013 classroom survey in which 26 Finnish university students were asked about their motives for and ways of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 10 publications
1
31
0
2
Order By: Relevance
“…Their uses and meaning are more varied than their phatic nature might indicate. Looking at perhaps the most wellknown PDA, the Facebook Like button, Eranti and Lonkila 3 found that this simple tool plays a significant role in the maintenance of social ties. Thus, PDAs go far beyond the literal indication a user Likes or has a Favorite post as their nomenclature denotes.…”
Section: Paralinguistic Digital Affordancesmentioning
confidence: 99%
“…Their uses and meaning are more varied than their phatic nature might indicate. Looking at perhaps the most wellknown PDA, the Facebook Like button, Eranti and Lonkila 3 found that this simple tool plays a significant role in the maintenance of social ties. Thus, PDAs go far beyond the literal indication a user Likes or has a Favorite post as their nomenclature denotes.…”
Section: Paralinguistic Digital Affordancesmentioning
confidence: 99%
“…The second one has to do with the use of the "like" button on posts about unfortunate events (such as the death of Muhammad Ali): it appears that users "like" the fact that somebody has died. Facebook has already implemented buttons that express numerous sentiments, but media websites do not offer that option yet (Veikko & Markku, 2015).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…WTPE predicts that some users believe that online media messages (like articles in media websites) do not affect them but have a greater effect on others (Antonopoulos et al, 2015). The "like" button is a social plugin of Facebook which enables the linking of this particular social media with the websites (Veikko & Markku, 2015). This button is a recommendation system enabling users to express their preference over the content they consume, and at the same time distribute it to their connections on Facebook.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…I want to be notified if text is added or changed. 4. I always want to be notified, independent from the change (even for small changes like correcting typos).…”
Section: Procedure/data Collectionmentioning
confidence: 99%
“…Previous research centered around "likes" in social media has focused on attitudes and perceptions of the person giving or receiving "likes" ( [4], [15]) or the varied motivations that users might have for favoring or "liking" something on Twitter, which can signal many things [12]. Another study examined what makes people click "like" on Facebook [10] and found out that people click "like" to express either enjoyment or to please others depending on one's own emotional stability and self-esteem.…”
Section: Related Work/backgroundmentioning
confidence: 99%